Implications of a short carbon pulse on biofilm formation on mica schist in microcosms with deep crystalline bedrock groundwater - Nuppunen-Puputti, Maija; Kietäväinen, Riikka; Kukkonen, Ilmo; Bomberg, Malin (Frontiers in Microbiology, 2023)
Microbial life in the deep subsurface occupies rock surfaces as attached communities and biofilms. Previously, epilithic Fennoscandian deep subsurface bacterial communities were shown to host genetic potential especially for heterotrophy and sulfur cycling. Here we examined further how a short pulse of low molecular weight carbon compounds impacts the formation and structure of sessile microbial communities on mica schist surfaces over an incubation period of ~3.5 years in microcosms containing deep subsurface groundwater from the depth of 500 m, from Outokumpu, Finland. Acetate, methane and methanol link multiple biogeochemical pathways and thus represent an important carbon and energy source for microorganisms in the deep subsurface. Dissimilarities between planktic and sessile rock surface microbial communities were observed and supplied carbon substrates led to variation in the bacterial community composition. Indicator species for each supplied carbon compound were investigated. The marker gene copy counts in the water and rock phases were estimated with qPCR, which showed that bacteria dominated the mica schist communities with relatively high proportion of epilithic sulfate reducing bacteria in all microcosms. The dominant bacterial phyla in the microcosms were Proteobacteria, Firmicutes and Actinobacteria, whereas most fungal genera belonged to the Ascomycota and Basidiomycota.